Statistical projection of post-vaccination antibody kinetics between dosing schedules. Issue 32 (26th July 2019) - Almudevar, Anthony; Kaur, Ravinder; Pichichero, Michael
Abstract: Determining a recommended dosage schedule is a crucial component of vaccine administration, and is often subject to reassessment. Ideally, recommendations will be supported by multiple arm clinical trials. However, the considerable cost in both resources and time means that a method of predicting post-vaccine humoral antibody levels associated with a hypothetical schedule using data collected from a currently implemented schedule would be of significant benefit to vaccination practice. In this paper we propose such a methodology, which permits statistical estimation of the population mean and standard deviation of log transformed antibody titers of various post-vaccination time points of a hypothetical schedule, using a longitudinal sample of antibody titers from an observed schedule. The method is based on the decomposition of humoral antibody kinetic history into distinct phases, for example, peak phase, decay phase and post-booster phase. The method is feasible because each phase has its own discernable kinetic laws. Of particular interest will be estimation of antibody levels immediately preceding a booster dose (typically the lowest level attained during the schedule), and the antibody levels following a booster dose.